2010
DOI: 10.1186/1744-9081-6-9
|View full text |Cite
|
Sign up to set email alerts
|

Neurofeedback and biofeedback with 37 migraineurs: a clinical outcome study

Abstract: BackgroundTraditional peripheral biofeedback has grade A evidence for effectively treating migraines. Two newer forms of neurobiofeedback, EEG biofeedback and hemoencephalography biofeedback were combined with thermal handwarming biofeedback to treat 37 migraineurs in a clinical outpatient setting.Methods37 migraine patients underwent an average of 40 neurofeedback sessions combined with thermal biofeedback in an outpatient biofeedback clinic. All patients were on at least one type of medication for migraine; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 27 publications
0
46
0
2
Order By: Relevance
“…Very similar therapeutic approaches were used to ameliorate the symptoms of the aforementioned pain disorders. Previously, other researchers described the efficiency of NFB in reducing pain due to headaches, fibromyalgia, and other pain syndromes (Caro & Winter, 2011;Kayiran, Dursun, Ermutlu, Dursun, & Karamürsel, 2007;Kayiran, Dursun, Dursun, Ermutlu, & Karamürsel, 2010;Stokes & Lappin, 2010;Walker, 2011). Stokes reported that 70% of migraine patients experienced at least a 50% reduction in pain.…”
Section: Discussionmentioning
confidence: 99%
“…Very similar therapeutic approaches were used to ameliorate the symptoms of the aforementioned pain disorders. Previously, other researchers described the efficiency of NFB in reducing pain due to headaches, fibromyalgia, and other pain syndromes (Caro & Winter, 2011;Kayiran, Dursun, Ermutlu, Dursun, & Karamürsel, 2007;Kayiran, Dursun, Dursun, Ermutlu, & Karamürsel, 2010;Stokes & Lappin, 2010;Walker, 2011). Stokes reported that 70% of migraine patients experienced at least a 50% reduction in pain.…”
Section: Discussionmentioning
confidence: 99%
“…Carmen (2004) reported improvement of more than 90% in migraine sufferers who completed at least six sessions of HEG training. For Stokes and Lappin (2010), 70% of migraine patients experienced at least a 50% reduction in frequency on more than 1-year follow-up from a combination of 40 neurofeedback sessions combined with HEG training. Tansey (1991a) published four case reports.…”
Section: Headaches and Migrainementioning
confidence: 99%
“…Neurofeedback is biofeedback applied to the brain and the central nervous system (Hammond, 2006). Numerous quantitative studies have indicated that neurofeedback may be effective in ameliorating symptoms often rooted in traumatic experience such as depression and anxiety (Hammond, 2005), substance abuse (Kelley, 1997;Peniston & Kulkosky, 1999;Scott, Kaiser, Othmer & Sideroff, 2005), posttraumatic stress disorder (Peniston & Kulkosky, 1991;Smith, 2008), and somatic symptoms such as migraine headaches (Stokes & Lappin, 2010) and fibromyalgia (Mueller, Donaldson, Nelson, & Layman, 2001). However, there is a paucity of research exploring the factors that produce those positive outcomes.…”
mentioning
confidence: 99%